Isolation and identification of Xanthomonas axonopodis pv. phaseoli and Pseudomonas savastonoi pv. phaseolicola causing disease in common bean producing areas in Samsun province of Turkey - Murat Öztürk (Anadolu Tarım Bilimleri Dergisi, 2018)
In 2013-2014, surveys were conducted in order to investigate the presence of Xanthomonas axonopodis pv. phaseoli (Xap) (common blight) and Pseudomonas savastonoi pv. phaseolicola (Psp) (halo blight) in common bean producing areas of Samsun province. Eight Xap and 5 Psp isolates were identified from single isolated pure colonies of the bacteria by means of biochemical, pathogenicity, molecular and 16S rDNA sequencing studies. Phylogenetic tree analysis demonstrated that the isolates of Xap and Psp obtained were clustered with their type strains. Göynük 98 was the most susceptible cultivar to Xap and Psp isolates among the five common bean cultivars tested in pathogenicity assays and selected for virulence assays. This work proved the presence of both disease agents in Samsun province, which supplies about 20 % of the total fresh bean production in Turkey, with molecular studies for the first time.